Negotiating symbols across time & place - Yeo, Jesvin Puay-Hwa (2024)
Design elements in Chinese temples are used to explain the myth, as well as a record of the traditions and customs. In Singapore, there are a few Chinese temples than are built more than 100 years ago. Some of the design elements within them have lost its meaning due to the lack of proper archiving and documentation. Focusing on three Hokkien architectural-style temples in Singapore, this paper explores, archives and analyzes a series of architectural design elements through a four-steps approach. Focusing on the context, aesthetic and stylistic progression, it aims to strengthen the study of traditional visual culture that allows insights of Singapore origins. And also serves as a platform for better understanding of local culture materials that might reveal Singapore’s relations with China. As well as to stimulate interest and open up sufficient conditions for the development needs of the future generations.